(untitled) (Jurnal Pembangunan Sosial, 2015)
The objective of this study is to find out the disabilities students’ (deaf and dumb) understanding and acceptance towards counseling services. A case study qualitative approach was used using semi-structured interview. Studies carried out on eight deaf and dumb students at the special education school in the state of Kedah, Malaysia. The research sampels were given four counseling sessions by a registered trained counselor in using sign language during the counseling session. Video footage was used to analyse the process of counseling sessions and the semi-structured interviews. Results showed that the deaf and dumb student’s did not understand about counselling services when interviewed before the counseling was conducted. After going through four counseling sessions, all eight research sampels showed very positive acceptance towards the counseling services. Summary from the results shows that the deaf and dumb students positively accept counselling services when implemented using sign language.